The use of the truth and deception in dementia care amongst general hospital staff. (3rd August 2017) - Turner, Alex; Eccles, Fiona; Keady, John; Simpson, Jane; Elvish, Ruth
ABSTRACT: Objectives: Deceptive practice has been shown to be endemic in long-term care settings. However, little is known about the use of deception in dementia care within general hospitals and staff attitudes towards this practice. This study aimed to develop understanding of the experiences of general hospital staff and explore their decision-making processes when choosing whether to tell the truth or deceive a patient with dementia. Method : This qualitative study drew upon a constructivist grounded theory approach to analyse data gathered from semi-structured interviews with a range of hospital staff. A model, grounded in participant experiences, was developed to describe their decision-making processes. Findings : Participants identified particular triggers that set in motion the need for a response. Various mediating factors influenced how staff chose to respond to these triggers. Overall, hospital staff were reluctant to either tell the truth or to lie to patients. Instead, 'distracting' or 'passing the buck' to another member of staff were preferred strategies. The issue of how truth and deception are defined was identified. Conclusion: The study adds to the growing research regarding the use of lies in dementia care by considering the decision-making processes for staff in general hospitals. Various factors influence how staff choose to respond to patients with dementia and whether deception is used. Similarities and differences with long-term dementia care settings are discussed. Clinical and research implications include: opening up the topic for further debate, implementing staff training about communication and evaluating the impact of these processes.